2015
DOI: 10.1590/1678-7153.201528301
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Necessidade de Cognição (NCS-18): Efeito de Itens Negativos em sua Estrutura Fatorial

Abstract: ResumoEste estudo objetivou testar a dimensionalidade da Escala de Necessidade de Cognição (NCS-18), controlando o efeito dos itens negativos. Participaram 215 estudantes universitários de João Pessoa (PB), com média de idade de 20 anos (DP = 3,79), os quais responderam a NCS-18 e questões demográfi cas. Testaram-se três modelos: M1 (modelo unifatorial convencional), M2 (modelo bifatorial, com itens positivos e negativos saturando em fatores separados) e M3 (modelo unifatorial, sendo controlado o efeito de ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Since its development, the two articles that introduced the long and short version of need for cognition (Cacioppo & Petty, 1982; Cacioppo et al, 1984) have together been cited more than 8,600 times (Google Scholar, April 2017), attesting to the measure’s importance and popularity in scientific research. Researchers have since then validated the NCS-34 and NCS-18 in various languages and/or countries, including Australia (Forsterlee & Ho, 1999), Germany (Bless, Wänke, Bohner, Fellhauer, & Schwarz, 1994), Greece (Georgiou & Kyza, 2019), Spain (Gutiérrez-Maldonado, Bajén, Sintas, & Amat, 1993), Taiwan (Kao, 1994), Portugal (Silva & Garcia-Marques, 2013), Netherlands (Pieters, Verplanken, & Modde, 1987), Brazil (Gouveia, Mendes, Soares, Monteiro, & Santos, 2015), and in a U.S.-Hispanic sample (Culhane, Morera, & Hosch, 2004), and it has been adapted to different populations, including children and adolescents (Keller et al, 2019). The NCS consistently exhibited high internal consistencies, with reliabilities generally varying between α = .80 and α = .90 (Cacioppo et al, 1996), and was found to be invariant across age groups (Soubelet & Salthouse, 2016).…”
Section: Need For Cognition Scalementioning
confidence: 99%
“…Since its development, the two articles that introduced the long and short version of need for cognition (Cacioppo & Petty, 1982; Cacioppo et al, 1984) have together been cited more than 8,600 times (Google Scholar, April 2017), attesting to the measure’s importance and popularity in scientific research. Researchers have since then validated the NCS-34 and NCS-18 in various languages and/or countries, including Australia (Forsterlee & Ho, 1999), Germany (Bless, Wänke, Bohner, Fellhauer, & Schwarz, 1994), Greece (Georgiou & Kyza, 2019), Spain (Gutiérrez-Maldonado, Bajén, Sintas, & Amat, 1993), Taiwan (Kao, 1994), Portugal (Silva & Garcia-Marques, 2013), Netherlands (Pieters, Verplanken, & Modde, 1987), Brazil (Gouveia, Mendes, Soares, Monteiro, & Santos, 2015), and in a U.S.-Hispanic sample (Culhane, Morera, & Hosch, 2004), and it has been adapted to different populations, including children and adolescents (Keller et al, 2019). The NCS consistently exhibited high internal consistencies, with reliabilities generally varying between α = .80 and α = .90 (Cacioppo et al, 1996), and was found to be invariant across age groups (Soubelet & Salthouse, 2016).…”
Section: Need For Cognition Scalementioning
confidence: 99%
“…The negative items disturb the factorial structure of theoretical models since they give rise to a new factor when it is not theoretically expected or justified (Ye, 2009). From the respondents' point of view, according to some authors (e.g., Moraes & Primi, 2002), questionnaires with negative items, require more attention and understanding by the subjects, which may explain the distinction of variability between the positive and the negative items, because, instead of presenting a clear answer, they appear as denial (Gouveia, Mendes, Soares, Monteiro, & Santos, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that this item presented a low intercorrelation (0.05) with the remaining items of the factor Desire for Understanding. Although the literature suggests the use of negative items (Pedhazur & Schmelkin, 1991; Spector, 1992), their application should be limited due to difficulties participants may encounter in processing the content and issuing a response (Gouveia, Lima, Gouveia, Freires, & Barbosa, 2012; Gouveia, Mendes, Soares, Monteiro, & Santos, 2015; Schmitt & Stuits, 1985). This situation may be due to multiple factors that could be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%